Activation of Bone Marrow-Derived Microglia Promotes Photoreceptor Survival in Inherited Retinal Degeneration - Sasahara, Manabu (American Society for Investigative Pathology, 2008)
The role of microglia in neurodegeneration is controversial, although microglial activation in the retina has been shown to provide an early response against infection, injury, ischemia, and degeneration. Here we show that endogenous bone marrow (BM)-derived microglia play a protective role in vascular and neural degeneration in the retinitis pigmentosa model of inherited retinal degeneration. BM-derived cells were recruited to the degenerating retina where they differentiated into microglia and subsequently localized to the degenerating vessels and neurons. Inhibition of stromal-derived factor-1 in the retina reduced the number of BM-derived microglia and accelerated the rate of neurovascular degeneration. Systemic depletion of myeloid progenitors also accelerated the degenerative process. Conversely, activation of BM-derived myeloid progenitors by systemic administration of both granulocyte colony-stimulating factor and erythropoietin resulted in the deceleration of retinal degeneration and the promotion of cone cell survival. These data indicate that BM-derived microglia may play a protective role in retinitis pigmentosa. Functional activation of BM-derived myeloid progenitors by cytokine therapy may provide a novel strategy for the treatment of inherited retinal degeneration and other neurodegenerative diseases, regardless of the underlying genetic defect.